K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

2 tháng 10 2017

C1: = x(x - 2) + y (x- 2)

= (x + y)(x - 2)

c2: x(x + y) -2 (x + y)

= (x + y)(x - 2).

1 tháng 9 2020

3x( y + 2 ) - 3( 1 - 2x ) ( như này đúng k -..- )

= 3( xy + 2x ) - 3( 1 - 2x )

= 3[ xy + 2x - ( 1 - 2x ) ]

= 3( xy + 2x - 1 + 2x )

= 3( xy + 4x - 1 )

x2 - y2 - 2x + 2y 

= ( x2 - y2 ) - 2( x - y )

= ( x - y )( x + y ) - 2( x - y )

= ( x - y )( x + y - 2 )

2x + 2y - x2 - xy

= 2( x + y ) - x( x + y )

= ( x + y )( 2 - x )

2 tháng 10 2016

a) \(x^2-2x-y^2+2y\)

\(=\left(x^2-y^2\right)-\left(2x-2y\right)\)

\(=\left(x-y\right)\left(x+y\right)-2\left(x-y\right)\)

\(=\left(x-y\right)\left(x+y-2\right)\)

b) \(2x+2y-x^2-xy\)

\(=2\left(x+y\right)-x\left(x+y\right)=\left(x+y\right)\left(2-x\right)\)

16 tháng 4 2017

x2-y2 -2x+2y=(x+y)(x-y)-2(x-y)=(x-y)(x-y-2)

2(x+y)-x(x+y)=(x+y)(2-x)

14 tháng 8 2016

1/ x(y+2) -2(y+2)=(y+2)(x-2)

2/ 2(x-y) - (x-y)= (x-y)(2-x+y)

24 tháng 7 2019

\(b,x^2+y^2-2x-2y-2xy\)

\(=\left(x-y\right)^2-2\left(x-y\right)\)

\(=\left(x-y\right)\left(x-y-2\right)\)

18 tháng 8 2020

a)

\(=x^2\left(2x+3\right)+\left(2x+3\right)\)

\(=\left(x^2+1\right)\left(2x+3\right)\)

b)

\(=a\left(a-b\right)+a-b\)

\(=\left(a+1\right)\left(a-b\right)\)

c)

\(=2\left(x^2+2x+1-y^2\right)\)

\(=2\left(x+1-y\right)\left(x+1+y\right)\)

d)

\(=x^3\left(x-2\right)+10x\left(x-2\right)\)

\(=x\left(x^2+10\right)\left(x-2\right)\)

e)

\(=x\left(x^2+2x+1\right)\)

\(=x\left(x+1\right)^2\)

f)

\(=y\left(x+y\right)-\left(x+y\right)\)

\(=\left(y-1\right)\left(x+y\right)\)

18 tháng 8 2020

a,2x3+3x2+2x+3

=(2x3+2x)+(3x2+3)

=2x(x2+1)+3(x2+1)

=(x2+1)(2x+3)

b,a2-ab+a-b

=(a2-ab)+(a-b)

=a(a-b)+(a-b)

=(a-b)(a+1)

c,2x2+4x+2-2y2

=2(x2+2x+1-y2)

=2[(x2+2x+1)-y2 ]

=2[(x+1)2-y2 ]

=2(x+1-y)(x+1+y)

d,x4-2x3+10x2-20x

=(x4-2x3)+(10x2-20x)

=x3(x-2)+10x(x-2)

=(x-2)(x3+10x)

=(x-2)[x(x2+10)]

e,x3+2x2+x

=x(x2+2x+1)

=x(x+1)2

f,xy+y2-x-y

=(xy+y2)-(x-y)

=y(x+y)-(x+y)

=(x+y)(y-1)

23 tháng 10 2016

a) \(\left(x^2-2x+1\right)-\left(y^2+2y+1\right)\)

\(=\left(x-1\right)^2-\left(y+1\right)^2\)

\(=\left(x-y-2\right)\left(x+y\right)\)

23 tháng 10 2016

b) xy+y2 = y ( x + y )

c) \(=\left(x^2+4xy+4y^2\right)-25\)

\(=\left(x+2y\right)^2-5^2\)

\(=\left(x+2y+5\right)\left(x+2y-5\right)\)

15 tháng 8 2016

x^2 + 3xy+2y^2 = x^2 +2xy+y^2+xy+y^2=(x+y)^2 + y(x+y)=(x+y)(x+2y)
 

21 tháng 11 2016

mẹ đi cày

14 tháng 8 2016

9(a-b)2-4(x-y)2

= [3(a-b)]^2 - [2(x-y)]^2

= [3(a-b) - 2(x-y)] [3(a-b) + 2(x-y)]

= (3x - 3b - 2x + 2y) (3a - 3b + 2x - 2y)